Deep bite correction with an anterior bite plate in a growing patient - Dwita Pratiwi; Miesje K Purwanegara (Wolters Kluwer Medknow Publications, 2020)
Background: Deep bites represent one of the most difficult cases in orthodontic treatment. In growing patients, strategies for deep bite correction include extrusion of posterior teeth and intrusion of incisors, which can be achieved using anterior bite plates. This case report presents the treatment of a deep bite in a growing patient using an anterior bite plate. Case Report: A 13-year-old female presented with a convex profile, short lower facial height, a Class II skeletal relationship, a deep bite (6 mm overbite), a 6 mm overjet, and severe crowding on both arches. The patient was treated with a removable anterior bite plate in conjunction with a fixed appliance. A normal overbite (2 mm) was achieved, severe crowding was corrected on both arches, the lower facial height was increased, the interincisal angle remained favorable, the mandibular incisors were well positioned in the basal bone, and the smile esthetics improved. Conclusion: The use of an anterior bite plate in combination with fixed appliances is effective in treating deep bites in a growing patient.